Strategi Peningkatan Baca Tulis Terhadap Warga Binaan di Lapas Perempuan Kelas II A Palembang - Suryati; Muzaiyanah; AdiSamudra (Social Science and Contemporary Issues Journal, 2024)
This research aims to analyze strategies for improving literacy for inmates in the Class II A Palembang Women's Prison. Literacy problems among inmates often become a major challenge in the rehabilitation and social reintegration process. The ability to read and write is a fundamental skill that is very important for individuals to participate fully in social life. However, not everyone has the same opportunity to develop this ability, including inmates in correctional institutions. This research is based on the fact that literacy problems are a challenge for inmates, especially in their rehabilitation and social reintegration process. Limited literacy can hinder their access to information, education and job opportunities after leaving prison. Therefore, this research aims to analyze strategies that can improve the reading and writing skills of inmates in class II A women's prisons in the city of Palembang. The research method used is a qualitative approach with descriptive research type. Data collection was carried out through interviews, observation and documentation of prison officers and several inmates who took part in the literacy program. The results of the research show that there are several strategies applied to improve literacy skills, such as telling the program objectives to the inmates and the benefits of the program, providing a comfortable learning environment for the inmates, providing direction to the inmates, providing action, providing relevant and interesting learning.